Real Options Analysis and Strategic Decision Making - Bowman, Edward H.; Moskowitz, Gary T. (Organization Science, 2001)
The real options approach is frequently advocated as an approach that offers a positive and radical reassessment of the value of risk and exploration. We examine a recent case where Merck used the real options approach to justify an investment in an R&D project. This case is used to highlight some of the problems associated with using real options. We note that the assumptions incorporated in most standard option valuation models can conflict with the conclusions reached by strategic analysis. As a result, users of real options models should understand the quantitative aspects of these models, and may often need to create a customized model for each situation. The difficulty of developing customized models may explain, in part, the limited use of the real options approach in strategic analysis.